2021
DOI: 10.3390/agriculture11090876
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of Vermicomposting in the South Pacific Island Countries: A Review

Abstract: Incorporation of vermin culture in the composting system produces “vermicompost”, an enriched biofertilizer known to improve the physical, chemical, and biological properties of soil. It is applied in granular form and/or in liquid solution (vermiwash), and in both open fields and greenhouses. Vermicompost has been shown to contain plant growth hormones, which stimulate seed germination and improve crop yield, the ‘marketability’ of products, plant physiology, and their ability to fight against disease. In rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…It has also been reported that VC usually contains more nutrients than plant-derived organic matter, and large amounts of these nutrients have been converted into forms that are easily absorbed by plants [10]. On the other hand, VC has high microbial and enzymatic activity and contains large amounts of plant growth regulators [11]. Continuous and adequate use of VC along with proper management can increase organic carbon storage and retain water in soils.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that VC usually contains more nutrients than plant-derived organic matter, and large amounts of these nutrients have been converted into forms that are easily absorbed by plants [10]. On the other hand, VC has high microbial and enzymatic activity and contains large amounts of plant growth regulators [11]. Continuous and adequate use of VC along with proper management can increase organic carbon storage and retain water in soils.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reviews and meta-analyses have summarized the beneficial effects of vermicompost-use in different farming systems, which also indicates directions for further studies of critical importance [5,[12][13][14][15]. Organic agriculture and horticulture are especially important targets for vermicompost application, in a view of providing balanced nutrition for crop needs and soil sustainability through enhanced microbiological activity [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Pierre-Louis et al 47 revealed the potentiality of vermicomposting in the South Pacific island countries. Vermicomposting improves the secretion of plant hormones activating the seed germination thereby improving the plant physiology, crop yield, and their capability to fight against disease.…”
Section: Vermicomposting Process Using Different Agro-residuesmentioning
confidence: 99%